The effect of the addition of metakaolin on the fresh and hardened properties of blended cement products : A review - Ayman, Mohammad Mansour; Al Biajawi, Mohammad Ismail Yousef (Elsevier Ltd, 2022)
Globally, cement is only second to water as the most consumed material with over 6 billion tons being produced every year. However, it is the most energy-intensive and expensive component of concrete. This study reviews the research carried out on the use of metakaolin as a Supplementary Cementitious Material (SCM) in paste, mortar, or concrete. The characteristics of metakaolin and its influence on the fresh and hardened properties of blended cement mixtures are demonstrated based on the recent literature. The review reported three main aspects of metakaolin-cement blends which are: physical (workability and setting times), mechanical (compressive strength and shrinkage), and long-term durability properties (chloride ion diffusion, sulfate attack resistance, and Alkali-Silica/-Carbonate Reaction (ASR/ACR). According to the literature, metakaolin is demonstrated as an effective pozzolan that improves the pore structure significantly. It can greatly enhance early age strength in blended cement products with no degradation, and potentially some improvement too, in long-term strength, all while improving permeability and resistance against ASR/ACR and the intrusion of harmful solutions.